Periprosthetic Joint Infection: Modern Aspects of Prevention, Diagnosis, and Treatment - Frank, Rachel M.; Cross, Michael B.; Della Valle, Craig J. (The Journal of Knee Surgery, 2015)
Periprosthetic joint infection (PJI) following total joint arthroplasty (TJA) is a devastating complication. Despite improvements in our understanding of PJI, the prevalence of this complication has not decreased in recent years, with various authors reporting rates of 1 to 2% after primary TJA and up to 7% following revision TJA. While the volume of publications, symposiums, and presentations on PJI is vast, controversy still remains regarding the prevention, diagnosis, and treatment of patients with PJI. The purpose of this article is to provide a succinct summary of the recent literature on the diagnosis, treatment, and prevention of a PJI after TJA.
Keywords: periprosthetic joint infection; total joint arthroplasty; diagnosis; revision